Faktor - Faktor yang Mempengaruhi Produksi Usahatani Tembakau di Gampong IE Alang Lamghui Kecamatan Kuta Cot Glie, Kabupaten Aceh Besar - Ruhsan Firdaus; Sri Fitri; Khumaira (Jurnal Agrisep, 2026)
Tobacco is a vital agricultural commodity in the country's economy and is a plantation commodity with significant potential. Its significance as a raw material for businesses that produce foreign currencies through exports, as a source of governmental revenue through taxes and excise, and as a source of employment and income for farmers are all clear indications of its function. One of the biggest tobacco-producing regions is Ie Alang Lamghui Village in Kuta Cot Glie District. The purpose of this study is to examine the variables affecting tobacco production. A quantitative approach using the Cobb-Douglas production function was used. Data were collected through observation and questionnaire-based interviews with 28 tobacco farmers. Data were analyzed using partial t-tests and natural logarithms using multiple linear regression. The research findings indicate that the variables tobacco seeds (X₁), land area (X₃), manure (X₄), and ZA fertilizer (X₆) have a positive and significant effect on tobacco production. Meanwhile, the variables of labor (X₂) and pesticides (X₅) did not have a significant effect. The highest coefficient value was obtained in the variables of ZA fertilizer and manure, which shows the importance of nutrients and soil fertility in increasing production results.